Effect of citric acid, herbal feed additive and their combination on the performance of broiler (Bangladesh Journal of Animal Science, 2016)
The experiment was conducted with 108 day old straight-run Hubbard Classic broiler chicks for a period of 35 days to investigate the effects of citric acid, commercial herbal additive (Keqinling) and their combination on growth and carcass traits of broiler. The dietary treatments were control (T0), 0.5% citric acid (T1), 0.2% Keqinling (T2) and combination of 0.5% citric acid +0.2% Keqinling (T3).  Final live weight was 1615, 1710, 1707 and 1795g in control, 0.5% citric acid, 0.2% Keqinling and their combination groups respectively. The highest live weight gain (1748g) was found in combination group followed by 0.5% citric acid (1664g), 0.2% Keqinling (1660g), and the lowest (1568g)in control group. The highest feed consumption and feed conversion efficiency was observed in T3 and the lowest in group T0. Significantly (p